OAK-D as a Platform for Human Movement Analysis: A Case Study - Perazzo, Daniel; Soares, Natalia Souza; Lyra, Victor Gouveia de Menezes; Lima, Gustavo Camargo Rocha; Fontes da Gama, Alana Elza; Xavier Natario Teixeira, Joao Marcelo; Teichrieb, Veronica (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2021: Anais do XXIII Simpósio de Realidade Virtual e Aumentada, 2021)
3D interaction is an essential manner of interaction in VR environments. Many devices enable analysis and use of human inputs in these settings, such as the Kinect™ from Microsoft. One of the latest additions is the OpenCV AI Kit with Depth or OAK-D. This paper analyzes the OAK-D and proposes a case study based on a Motion Analysis framework created for at-home workouts to explore its capabilities in a 3D interaction setting. Our results show that the OAK-D is well suited for this kind of task, achieving 7 FPS with a Raspberry Pi 4 and 15 FPS with a laptop. Furthermore, it could detect and correct wrong movements while the user was doing it and count repetitions for the squat and side lateral raise.